Transmission of bovine viral diarrhea virus among white-tailed deer (Odocoileus virginianus) - Passler, Thomas (EDP Sciences, 2009)
Cattle persistently infected (PI) with bovine viral diarrhea virus (BVDV), a pestivirus in the family Flaviviridae, are an important source of viral transmission to susceptible hosts. Persistent BVDV infections have been identified in white-tailed deer (Odocoileus virginianus), the most abundant free-ranging ruminant in North America. As PI deer shed BVDV similarly to PI cattle, maintenance of BVDV within white-tailed deer populations may be possible. To date, intraspecific transmission of BVDV in white-tailed deer has not been evaluated, which prompted this study. Six pregnant white-tailed deer were captured in the first trimester of pregnancy and cohabitated with a PI white-tailed deer. Cohabitation with the PI deer resulted in BVDV infection in all does, as indicated by seroconversion. All does gave birth to live fawns and no reproductive losses were observed. At birth, evidence of BVDV infection was identified in two singlet fawns, of which one was determined to be PI by repeated serum reverse transcription nested PCR, whole blood virus isolation and immunohistochemistry. This study demonstrates for the first time that BVDV transmission may occur among white-tailed deer. The birth of a PI fawn through contact to a PI white-tailed deer indicates that under appropriate circumstances, BVDV may be maintained in white-tailed deer by congenital infection.